The battle of YouTube, TV and Netflix: An empirical analysis of competition in audio-visual media markets - Oliver Budzinski; Sophia Gänßle; Nadine Lindstädt-Dreusicke (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2020)
The world of audiovisual online markets is rapidly changing. Not long ago, it was dominated by linear television, transmitted terrestrially, through cable networks or via satel-lite. Recently, streaming services like Netflix, YouTube, Amazon Prime and others have emerged as new suppliers of audiovisual content. In this quickly changing industry, compe-tition interrelations between such different formats like traditional TV, videos on YouTube, and streaming via Netflix are subject to controversy. In particular, doubt is cast on services like YouTube exerting competitive pressure on services like Netflix and traditional TV. Based upon a survey with almost 3,000 participants, we provide an empirical analysis of consump-tion behavior of audiovisual contents. Using descriptive and analytical statistics, including multiple equation models, we show that there are specific areas within audiovisual content markets where YouTube exerts considerable competitive pressure on both Netflix and classic TV, for instance, through prime time video entertainment. However, our analysis yields dif-ferentiated results as we also identify areas where competition intensity between different service types appear to be low, for instance, through daytime and regarding the intention to shorten waiting time.
Keywords: L82; L86; Z10; M21; L13; L40; L51; C39; 330; video-on-demand; streaming markets; media economics; cultural economics; commercial television; multiple equation models; competition; consumption behavior